BANKS’ COMMITMENT TO THEIR PRINCIPLES AS A STRATEGY TO ENHANCE CUSTOMER LOYALTY: THE MODIFYING ROLE OF BANKING TALENT - Odeesh, James (Humanities Journal of University of Zakho, 2024)
The study seeks to realize the role that the presence of banking talent plays in enhancing the relationship between commitment to banking principles and customer loyalty. To achieve this goal, SPSS program (version 26) was used to analyze the data collected through a questionnaire, distributed to a sample of 160 customers, who were systematically selected from Dasnia Bank in Dohuk Governorate, represented by the human resources working in the presidency of Duhok Polytechnic University, Technical College of Engineering, and Technical Institute in Sinjar, where human resources deal with Dasnia Bank. Totally, 153 copies of the questionnaire were received to analyze the data statistically between banks’ commitment to their principles (independent variable) and customers’ loyalty to banks (dependent variable), as well as the modifying variable determined by the presence of banking talent. Based on the results of the analysis, a number of conclusions were reached. The findings indicated that Dasnia Bank follows good banking practices, which makes customers more loyal. It also helps if there are good bankers in the company. Therefore, it is important to have someone who has the skills, abilities, and experience needed to work in banking. This helps banks stay true and loyal to their principles. Finally, the study recommended the need for Dasnia Bank and other banks to rely on the default model, which succeeded in clarifying a relationship of influence of banks commitment to the principles on the loyalty of customers.